Why differentiating between health system support and health system strengthening is needed. (9th July 2012) - Chee, Grace; Pielemeier, Nancy; Lion, Ann; Connor, Catherine
SUMMARY: There is increasing recognition that efforts to improve global health cannot be achieved without stronger health systems. Interpretation of health system strengthening (HSS) has varied widely however, with much of the focus to‐date on alleviating input constraints, whereas less attention has been given to other performance drivers. It is important to distinguish activities that support the health system, from ones that strengthen the health system. Supporting the health system can include any activity that improves services, from distributing mosquito nets to procuring medicines. These activities improve outcomes primarily by increasing inputs. Strengthening the health system is accomplished by more comprehensive changes to performance drivers such as policies and regulations, organizational structures, and relationships across the health system to motivate changes in behavior and/or allow more effective use of resources to improve multiple health services. Even organizations that have made significant investments in health systems have not provided guidance on what HSS entails. While both supporting and strengthening are important and necessary, it is nonetheless important to make a distinction. If activities fail to produce improvements in system performance because they were incorrectly labeled as system strengthening, the value of HSS investments could quickly be discredited. Not distinguishing supportive activities from strengthening ones will lead to unmet expectations of stronger health systems, as well as neglect of critical system strengthening activities. Distinguishing between these two types of activities will improve programming impact. Copyright © 2012 John Wiley & Sons, Ltd.